2013
DOI: 10.1007/s00167-013-2384-4
|View full text |Cite
|
Sign up to set email alerts
|

Validity of GNRB® arthrometer compared to Telos™ in the assessment of partial anterior cruciate ligament tears

Abstract: The diagnostic value of GNRB(®) was better than Telos™ for ACL partial thickness tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 25 publications
(37 reference statements)
1
38
1
5
Order By: Relevance
“…A laximetry test (GNRB arthrometer) was also performed. This method was seen as preferable to the Telos one since it provided a better sensitivity and specificity [14].…”
Section: Populationmentioning
confidence: 99%
“…A laximetry test (GNRB arthrometer) was also performed. This method was seen as preferable to the Telos one since it provided a better sensitivity and specificity [14].…”
Section: Populationmentioning
confidence: 99%
“…In the 1980s, this characteristic was shown to be modified in the ACL-injured knee [72,75], but its use in the diagnosis of ACL injuries has only been recently proposed [15,76]. To further improve the diagnosis of ACL injuries, consideration of the slope is advised as it has been shown to increase the specificity of anterior and rotational knee laxity tests to 100 %.…”
Section: Knee Laxity In the Injured Knee Diagnosis Of Acl Injuriesmentioning
confidence: 99%
“…Based on arthroscopy, it is however possible to differentiate partial tears (the antero-medial bundle being more often concerned than the posterolateral one) from complete ACL lesions presenting either as a totally resorbed ligament or as a healed remnant on the intercondylar notch or the PCL [78]. These different lesions influence the SSD observed in anterior and rotational knee laxity measurements [76,[79][80][81][82]. As such, only considering complete tears to evaluate the diagnostic performance of an arthrometer cannot reflect its true diagnostic capacity.…”
Section: Further Considerations For Diagnosismentioning
confidence: 99%
“…The GNRB ® device used here has good reproducibility, good accuracy (0.1 mm), and is non-irradiating [19][20][21]. In the current study, knee laxity measurements helped to confirm the diagnosis of ACL rupture and were able to significantly differentiate between partial and complete ruptures.…”
Section: Discussionmentioning
confidence: 82%
“…In the current study, 72% of ruptures were detected at this threshold. Lefèvre et al [21] showed that the diagnostic value of the GNRB ® at 250 N was better than with the Telos ® for the diagnosis of partial ruptures. With a threshold of 2.5 mm at 250 N, 83% of ruptures were correctly classified.…”
Section: Discussionmentioning
confidence: 99%